Nutritional studies of Chara corallina - Singh, Uday Bhan; Thakur, R K; Verma, Ravish; Ahluwalia, A S (Recent Research in Science and Technology, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Physico-chemical analysis of the pond water supporting growth of Chara corallina and of those grown in different culture media in the laboratory conditions have been carried out. The physico-chemical parameters of the water of Napli forest and P.N. Mehra Botanical Garden show that Chara corallina requires less amount of nutrients and the level of pollution is quite low as is evident from the data and standards. The water is clear enough to allow penetration of visibility to its bottom. Napli forest and P.N. Mehra Botanical Garden lack rich diversity which may be attributed to some chemicals released by Chara corallina. In laboratory culture, it is found that Chara corallina can be grown in all three culture media, viz., Allen and Arnon’s medium , Chu-10 medium and BG-11 medium but growth is seen to be the best in Allen and Arnon’s culture medium in comparison with the other two culture media.